STUDI LITERATUR TENTANG PERSEPSI “MARRIAGE IS SCARY” DALAM FENOMENA WAITHOOD PADA GENERASI Z. - Rafa Nur Fatihah; Sujarwo Sujarwo; Desy Safitri (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study aims to determine the perception of "Marriage is Scary" in the waithood phenomenon among Generation Z, as well as to identify the causal factors and their impact on the tendency to delay marriage. The research method used is a qualitative method with a literature study approach, which was carried out through the collection and analysis of various relevant national journal sources. Data analysis in this study was carried out by identifying, grouping, and synthesizing findings from previous studies related to the research topic. The results show that the perception of "Marriage is Scary" is influenced by social media, indirect experiences related to household conflict, as well as economic factors and individual readiness. This perception forms a more critical view of marriage and contributes to the emergence of the waithood phenomenon as a form of marriage delay among Generation Z.